(untitled) (Revista Apotheke, 2025)
Instead of a strictly linear and sequential History of Art (ordered by dating of movements, trends, artists or styles), we should conceive of certain genealogies of artists who, despite being active in very different or distant times, reveal similar or invariant characteristics, where these invariants trace a trend that is beyond a precise or restricted time; equivalent to saying, something to be developed, that classicism is understood in the understanding of the study of works such as those of Rafael, Poussin or Ingres, which leads us to the study of remarkable facts from the 16th century (Rafael) to the 19th century (Ingres). The same could be said of the “modern spirit”: taking Picasso, one hypothesis among others, but a credible hypothesis, taking Picasso, I said, as the central figure of the modern, at the beginning of the 20th century, we will be able to see how it is formed, or how modernity is formed after its “Blue Period”, a time immediately after the author’s training period. And this is after to the “Black Spain” (España Negra) movement of Gutiérrez Solana, Darío Regoyos, Zuloaga and Nonell. In the genealogical reading of History (of a non-sequential History of Art), the “Black Spain” movement, following Walter Benjamin’s idea of looking at History “against the grain” (working History from the present to the past), confirms the Goya’s modernity, and thus we will have established the genealogy of modernity: Goya (who, in turn, confirms the modernity of El Greco, to establish a root of the modern), “repeats himself” in “Black Spain” and this generates Picasso from the “Blue Period. Goya-“Black Spain”-Picasso are to modernity what Rafael-Poussin-Ingres-Salon Academism are to classicism, or “classical spirit”.